2016
DOI: 10.1007/s40726-016-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and the Terrestrial Nitrogen Cycle: A Review

Abstract: The distribution, fate, and effects of human and veterinary antibiotics in the environment have been the subject of intense investigation for nearly two decades. Studies show that the structure and function of microbial communities in soil and sediment are modified by antibiotic exposure but the resulting impact on biogeochemical processes is poorly understood. This review summarizes the most recent data on the present use and physicochemical properties of human and veterinary antibiotics and provides an overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 132 publications
(98 reference statements)
1
34
0
2
Order By: Relevance
“…Our study also revealed that, none of the farmers ever screened their manure for antibiotic residue. A number of studies have reported substantial quantities of antibiotic in manure [9,10] posing a threat to the environment. Manure is a major soil nutrient source for farmers in Ghana and it is obvious that farmers might have introduced antibiotic into the environment through the application of manure to agricultural field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study also revealed that, none of the farmers ever screened their manure for antibiotic residue. A number of studies have reported substantial quantities of antibiotic in manure [9,10] posing a threat to the environment. Manure is a major soil nutrient source for farmers in Ghana and it is obvious that farmers might have introduced antibiotic into the environment through the application of manure to agricultural field.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, revealed that farmers were bereft of knowledge regarding antibiotic effect on soil properties and processes. Some effects for which farmers showed inadequate knowledge were; substantial quantity of antibiotic given to animals end up in manure [9,10], antibiotics cause the death/inhibit growth of microbial groups involved in ecosystem functions [44], antibiotics affect bacteria/fungi ratio in soil [8], high antibiotic rate decrease soil respiration/catabolism' [45], high antibiotic rate influence nutrients transformation and decrease nitrification in nitrogen cycle [21], Other effects considered with inadequate knowledge were; antibiotics compete with other soil cations/anions for exchange site [22,46], which could lead to enhanced mobility and possible leaching of essential soil macro nutrients such as Mg 2+ and Ca 2+ , increase ARGs in soil [12,13]. The low level of knowledge on the effect of antibiotic laden manure will perpetuate resistance development and negatively influence soil quality and food security.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from McFarland et al (1997); Nowara et al (1997); Rabølle and Spliid (2000); Thiele (2000); Kümmerer (2001); Tolls (2001); Boxall et al (2002, 2006); Hamscher et al (2002, 2005); Thiele-Bruhn (2003); Jacobsen et al (2004); Kay et al (2004, 2005); Thiele-Bruhn et al (2004); Halling-Sørensen et al (2005); Kumar et al (2005a, 2012); Schmitt et al (2005); Thiele-Bruhn and Beck (2005); Sarmah et al (2006); Martínez-Carballo et al (2007); Sassman and Lee (2007); Stoob et al (2007); Aust et al (2008, 2010); Park and Choi (2008); Sukul et al (2008); Zhang and Dong (2008); Karci and Balcioglu (2009); Kuchta et al (2009); Li et al (2009, 2010a,b, 2011, 2015); Muñoz et al (2009); Conkle et al (2010); Hu et al (2010); Vazquez-Roig et al (2010); Watanabe et al (2010); Yang et al (2010, 2016); Zhao et al (2010); Fan et al (2011); Lin and Gan (2011); Rosendahl et al (2011); Zhou et al (2011, 2013b); Leal et al (2012); Pinna et al (2012); Shi et al (2012); Bak et al (2013); Huang et al (2013); Kang et al (2013); Wu et al (2013, 2014); Awad et al (2014); Chen et al (2014); Ho et al (2014); Pan et al (2014); Rutgersson et al (2014); Van Doorslaer et al (2014); Wegst-Uhrich et al (2014); Gao et al (2015); Hou et al (2015); Liu et al (2015); Wang and Wang (2015); DeVries and Zhang (2016); Pan and Chu (2016, 2017b); Tasho and Cho (2016); Zhang et al (<...>…”
Section: Introductionmentioning
confidence: 99%
“…Factoring in both various abiotic and biotic factors, which influence the behavior of the antibiotic in the soil, its degradation time (DT50 or half-life) may vary from less than one (e.g., amoxicillin) [10] up to 3466 (e.g., azithromycin) days [11]. In addition to antibiotics, bacterial strains resistant to these compounds may also enter the environment [12][13][14][15]. The consequences of such actions may be the development of antibiotic-resistant microorganisms [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%